Height of Transplants of Eucalyptus hybrid (SYN. E. Tereticornis) and Plantation Performance - Nair, N. R. (Indian Forester, 1971)
This paper deals with an experimental study conducted to investigate the influence or otherwise of the height of the transplants at the time of planting, on plantation performance in Eucalyptus tereticornis species. The study showed that the advantage in height growth of tall transplants over short. Transplants (within a range of 15 cm to 95 cm) persisted six months after planting out whereas there was no significant difference in height growth of the transplants of different heights after 37 months in the plantation. This indicates that the planting heights (within a range of 15 cm to 95 cm) influence the plantation heights during the early stages but the differences in height growth tend to even out in later years.